The transformative power of networking in the implementation of the Sustainable Development Goals - Walter Leal Filho; Barbara Fritzen; Amanda Lange Salvia; Maria Alzira Pimenta Dinis; Claudio R. P. Vasconcelos (Discover Sustainability)
Abstract Networks can help implement the United Nations Sustainable Development Goals (SDGs) in a variety of ways. They can facilitate the sharing of best practices and resources among organisations, enabling them to more effectively implement the SDGs. They can also help spread awareness on the SDGs and encourage people to take action. Networks can also assist coordinate collaborations between different organisations to support the SDGs implementation, especially in the academic sector. This study aims to fill the literature gap in assessing the transformative power of sustainability networking and reports on a worldwide analysis of the international networks which are believed to have been playing a significant role in the implementation of the SDGs in higher education. A concise online questionnaire was designed and administered to experts via an expert database mailing list and social networks, and collected 153 responses from 37 countries. This was complemented by an assessment of a set of case studies, where 5 major sustainability networks—ESSSR, IUSDRP, SDSN, AASHE and Copernicus Alliance—were evaluated in respect of their scope, target groups, types of activities and contributions to the SDGs. The results have highlighted the fact that, whereas assessed networks are very active, there is still a perceived need for more concerted actions to allow these networks to become more engaged in the implementation of the SDGs. This study suggests some specific actions which may foster a greater collaboration among networks in order to maximise the impact of their sustainability initiatives. The process of networking contributes to the advancement of sustainability and is closely related with contributions to policy, economic development and society, as well as particularly to SDG 17—Partnerships for the Goals. This study supports the role of networking, while indicating the need for greater collaboration among networks in order to maximise the impact of their initiatives and their transformative power.